The Effectiveness of Receivables Management and Efforts to Minimize Uncollectible Receivables in Indonesian Banking - Hilfa Mora Marito Nasution; Erwin Febriansyah; Muliawati Muliawati; Leni Cinda Winata (Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the effectiveness of receivables management in minimizing bad debts in Indonesian banking institutions. Bank receivables in the form of loans represent a major asset but also carry the risk of non-performing loans (NPL). The research uses a quantitative approach with panel data regression analysis. The population consists of banks registered with the Financial Services Authority and the Indonesia Stock Exchange during the 2021–2024 period. Using purposive sampling, 10 banks were selected, resulting in 40 observations. Model selection tests, including the Chow test and Hausman test, indicate that the fixed effect model is the most appropriate. The results show that receivables management has a significant negative effect on bad debts. The coefficient of determination of 0.87 indicates that receivables management strongly explains variations in bad debts. Both simultaneous and partial tests are statistically significant. These findings confirm that more effective receivables management leads to lower levels of bad debts, highlighting the importance for banks to strengthen credit policies, monitoring, and collection systems.